EFFECT OF BICLOTYMOL ON MOUTH CAVITY MUCOSAL MICROBIOTA IN CHILDREN - L. K. Katosova; A. V. Lazareva; O. A. Ponomarenko (Педиатрическая фармакология)
Introduction. Biclotymol [bis(chloro-4-thymol)methyl] is a biphenol derivative used for local treatment of pharyngeal inflammatory diseases. It is an antiseptic drug with bacteriostatic and bactericidal effects. Objective: evaluation of the drug’s antibacterial activity towards opportunistic and normal oropharyngeal microflora and identification of its minimum bactericidal concentration for the main bacterial pathogens of the upper respiratory tract. Results: we revealed that antibacterial effect of biclotymol on mouth cavity microbiota manifests itself with elimination of such species and genera of opportunistic microflora as Staphylococcus aureus, Streptococcus pyogenes, Haemophilus spp. and anginosus streptococci. We also revealed antibacterial activity of biclotymol against normal microbiota representatives, which included viridans streptococci. Out of this group of streptococci, only 1/3 of the initial amount of Streptococcus salivarius remained in place. Alongside identification of the minimum inhibitory concentration (MIC) of biclotymol against opportunistic microflora we revealed the most sensitive bacteria requiring the lesser drug concentration for the antibacterial effect to take place – Streptococcus pneumoniae and Haemophilus influenzae; intermediate – Moraxella catarrhalis, S. pyogenes and S. aureus; and resistant – non-pathogenic Neisseria species. Among the strains that survived biclotymol exposure, MIC was the highest in Neisseria spp. – 20 mg/ml after a 30‑minute-long exposure. Conclusions: results of a study of antibacterial effect of a topical antiseptic containing biclotymol demonstrated that the drug’s bactericidal activity is primarily aimed at gram-positive cocci represented both by opportunistic and non-pathogenic microbes. Non-pathogenic Neisseria species abundantly inhabiting mouth cavity mucosae and gram-negative rod-like microbes, which are uncharacteristic of the biotope under study, appeared to be resistant to bactericidal effect of biclotymol. Preservation of these microbes may somewhat prevent oropharyngeal colonization by undesirable pathogenic species.